Innovative factor of globalization processes development - Strunin, Viktor (My University, 2013)
The role of innovation and innovative activeness in the of globalization processes development was described. Висвітлено роль інновацій та інноваційної активності у розвитку глобалізаційних процесів.
Keywords: інновації (економіка); globalization; innovation (economics); глобалізація; кластер; кафедра економіки праці та менеджменту